The complete guide to the art of modern cookery : the first translation into English in its entirety of Le guide culinaire - Escoffier, A. (Auguste), 1846-1935 (SoFAB Culinary Collection., 2001)
Unlike a recipe book which leads the cook step by step, this work provides guidelines, ideas and techniques for the preparation and presentation of various foods.